Using circuit training and mini-game based sessions to assess the circulating leukocytes responsiveness to exercise among College soccer players in the subtropical environment. - Gouthon, Polycarpe; FALOLA, Jean-Marie; Bio Nigan, Issiako; Arèmou, Mansourou; DANSOU, HOUNDJOVI PIERRE; HOUSSOU, Roland (My University, 2013)
This experimental study aimed at comparing the variations of the circulating leukocytes within the 24 hours following an anaerobic circuit training session (CT), to those of an aerobic mini-game based session (AE) in the hot climate of Benin. In a random order, sixteen College soccer players (22.8 ± 0.5 years) took part in CT and AE training sessions, and a 5 hours rest (R5) was used as control. Blood samples were taken in the end, 6 and 24 hours after each session, 15 days apart. The circulating leukocyte counts were assessed by flow cytometry. Twenty-four hours after the training session, the subsequent effect (p < 0.05) was noticed for CD4 lymphocytes alone. After CT, no time measurement effect was seen for any sub-type of circulating leukocyte (p > 0.05). On the contrary, AE induced a significant increase (p < 0.05) in eosinophil and monocyte counts at the end of the session, followed 24 hours later by a return to the primary values. There was a significant decrease (p < 0.05) in neutrophil and CD4 lymphocyte counts during and 24 hours after the AE session. Considering the conditions under which this study was carried out, the AE session can be used for assessing the quantitative immune response to exercise in soccer players. However, the immune system requires more than 24 hours for recovering. The use of a CT session, i.e. resistance training, requires another experimental study for determining the suitable training design.
Keywords: Leukocyte count; aerobic training; circuit training; mini game; soccer; Benin.